Assessment of the Hematopoietic Cell Transplantation Comorbidity Index in Non-Hodgkin Lymphoma Patients Receiving Reduced-Intensity Allogeneic Hematopoietic Stem Cell Transplantation - Pollack, Seth M. (2009)
The hematopoietic cell transplantation comorbidity index (HCT-CI), a weighted index of 17 pretransplantation comorbidities, has been validated in nonmyeloablative and myeloablative allogeneic hematopoietic stem cell transplantation (HSCT) studies, but it has not been specifically tested in patients with non-Hodgkin lymphoma (NHL) receiving reduced-intensity conditioning (RIC). We performed a retrospective analysis to assess the impact of the HCT-CI on outcomes of NHL patients treated with HSCT relative to treatment-related mortality (TRM), disease-related mortality (DRM), with a specific emphasis on overall survival (OS). Individual pretransplantation and disease-related factors also were analyzed with HCT-CI relative to their impact on OS. All patients were uniformly treated with an identical pretransplantation induction regimen and an identical RIC regimen (cyclophosphamide [Cy]/fludarabine [Flu]), and received T cell–replete allografts from HLA-matched siblings. The analysis included 63 NHL patients with a median HCT-CI score of 2 (range, 0 to 11). The HCT-CI (0 to 2 comorbidities vs 3+ comorbidities) demonstrated a potential association with TRM, but not with DRM, at 100 days (4.5% vs 26.3%) and at 1 year (13.6% vs 36.8%) posttransplantation. The factor most strongly associated with OS was response to pretransplantation chemotherapy (P = .0001), based on a composite measure. In a Cox model, pretransplantation chemotherapy response remained the most important factor (P < .0001) relative to OS, and there was a trend (P = .056) toward HCT-CI adding predictive value for OS. Although HCT-CI may be useful for predicting TRM, our data further underscore the importance of response to chemotherapy before transplantation as a predictor of overall transplantation outcome in NHL patients being considered for RIC allogeneic HSCT.